SYSTEM INTERCONNECTION OF INFRASTRUCTURE PROJECTS ON WATER TRANSPORT - Верещака, Николай (SWorldJournal, 2020)
The article deals with the identification of systemic links of infrastructure projects, which is necessary to determine the factors affecting these projects, as well as the set of project stakeholders. As a result, systemic links of infrastructure project